2009
DOI: 10.1007/s11745-009-3380-9
|View full text |Cite
|
Sign up to set email alerts
|

Possible Biosynthetic Pathways for all cis‐3,6,9,12,15,19,22,25,28‐Hentriacontanonaene in Bacteria

Abstract: A very long chain polyunsaturated hydrocarbon, hentriacontanonaene (C31:9), was detected in an eicosapentaenoic acid (EPA)-producing marine bacterium, which was isolated from the mid-latitude seashore of Hokkaido, Japan, and was tentatively identified as mesophilic Shewanella sp. strain osh08 from 16S rRNA gene sequencing. The geometry and position of the double bonds in this compound were determined physicochemically to be all cis at positions 3, 6, 9, 12, 15, 19, 22, 25, and 28. Although C31:9 was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Hydrocarbon biosynthesis has been studied with bacteria of the genus Shewanella (7, 9). Shewanella oneidensis strain MR-1 produces a single polyolefinic hydrocarbon, 3,6,9,12,15,19,22,25,28-hentriacontanonaene, and contains the oleABCD genes.…”
Section: Observationmentioning
confidence: 99%
“…Hydrocarbon biosynthesis has been studied with bacteria of the genus Shewanella (7, 9). Shewanella oneidensis strain MR-1 produces a single polyolefinic hydrocarbon, 3,6,9,12,15,19,22,25,28-hentriacontanonaene, and contains the oleABCD genes.…”
Section: Observationmentioning
confidence: 99%
“…Various bacterial species belonging mostly to gammaproteobacteria are known to produce long‐chain polyunsaturated fatty acids (LC‐PUFAs). These bacteria are members of relatively restrictive genera, such as Shewanella , Photobacterium , Moritella , and Colwellia . Most of these LC‐PUFA‐producing bacterial species were isolated from cold marine environments: deep sea water and sediments, as well as the polar regions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these LC‐PUFA‐producing bacterial species were isolated from cold marine environments: deep sea water and sediments, as well as the polar regions. However, reports of LC‐PUFA‐producing bacteria isolated from marine temperate and even subtropical regions are also accumulating . Major LC‐PUFAs of these bacteria are eicosapentaenoic acid (EPA) and/or docosahexaenoic acid (DHA) and have been regarded as modulators of membrane fluidity due to their lower melting temperatures and thus the lower gel‐to‐liquid crystalline phase‐transition temperatures of the LC‐PUFA‐containing membrane phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hydrocarbons are present in most microorganisms, 3 but the capability to produce long chain PUFAs, such as the ω-3 PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), has mostly been reported for psychrophilic, piezophilic and some mesophilic (Shewanella sp.) [5][6][7] The positions and the Z-configuration of the nine double bonds as well as the structure of this un-branched very long-chain hydrocarbon (VLCH) 1 were assigned mainly on data obtained from FTIR and MS experiments. 4,5 Recently, it has been reported that the bacterial strains producing long-chain PUFAs are also characterized by the presence of a small amount of an uncommon polyolefin natural product, namely (all-Z)-hentriaconta-3, 6,9,12,15,19,22,25,28-nonaene (C31:9, 1), see Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…bacteria phyla. 5,7 Sukovich et al discussed that the C31:9 lipid 1 may be biosynthesized via a headto-head condensation pathway between two entities derived from (all-Z)-4,7,10,13-hexadecatetraenoic acid (2) (Scheme 1). [5][6][7] The positions and the Z-configuration of the nine double bonds as well as the structure of this un-branched very long-chain hydrocarbon (VLCH) 1 were assigned mainly on data obtained from FTIR and MS experiments.…”
Section: Introductionmentioning
confidence: 99%